Diffusion-weighted imaging as a follow-up modality for evaluation of major salivary gland function in nasopharyngeal carcinoma patients: a preliminary study. - Fan, Wen-jun; Teng, Feng; Luo, Yan-rong; Yu, Wei; Zhang, Qian; Lu, Yi-ping; Ma, Lin (Strahlentherapie und Onkologie, 2020)
Purpose: To investigate the value of diffusion-weighted imaging (DWI) in assessing dynamic changes of major salivary gland function during follow-up post radiotherapy (RT) in nasopharyngeal carcinoma (NPC) patients.Materials and Methods: 31 consecutive patients with pathologically confirmed NPC scheduled for RT underwent six routine follow-up MRI examinations including DWI sequence prior to (pre-RT) and 1, 3, 6, 9, and 12 months post RT. Mean apparent diffusion coefficient (ADC) values of bilateral parotid glands (PGs) and submandibular glands (SMGs) were measured. Objective measurement of salivary flow rate (SFR) under unstimulated (uSFR) and stimulated conditions (sSFR) as well as subjective xerostomia assessment according to a patient-rated questionnaire were conducted before each MRI. Variance analysis was used to evaluate dynamic changes of ADC, SFR and xerostomia questionnaire summary scores (XQ-sum) at different timepoints and the correlation between ADC and XQ-sum. Pearson's correlation test was used to evaluate the correlations between pre- and post-RT changes of ADC (ΔADC) and SFR (ΔSFR) or mean RT dose.Results: At each timepoint, ADCs of PGs were significantly lower than of SMGs, uSFR was significantly lower than sSFR. For both PGs and SMGs, ADCpost-RT were all higher than ADCpre-RT, with significant differences. ADC1m-post-RT initially increased and changed little to ADC3m-post-RT, ADC6m-post-RT, ADC9m-post-RT, and ADC12m-post-RT, then gradually declined over time. The dynamic change trends of SFR were negatively paralleled to those of ADC, while that of XQ-sum was similar. Dose-response relationships were detected between salivary gland mean RT dose and ΔADC. In PGs, negative correlations between ΔsSFR9m-post-RT and ΔADC9m-post-RT, and ΔsSFR12m-post-RT and ΔADC12m-post-RT were detected. In SMGs, negative correlations between ΔsSFR12m-post-RT and ΔADC12m-post-RT, and ΔuSFR12m-post-RT and ΔADC12m-post-RT were also detected. The ADCs of patients with severe subjective xerostomia were significantly higher, while patients with moderate subjective xerostomia presented a tendency toward higher ADCs compared to those with mild xerostomia from 6 to 12 months post RT.Conclusion: As part of routine follow-up MRI in NPC patients, DWI might be a promising modality for follow-up assessing the dynamic changes of major salivary gland function and might be more powerful in the late post-RT period.